A review of the economic contribution of pastoral production systems to the national economies in sub-Saharan Africa - Gebreselassie, N.; Desta, S.; Ehui, Simeon K. (International Livestock Research Institute, 1998)
The objective of this paper is therefore; to review the economic contribution of pastoral production system to the national economies in sub-Saharan Africa. The first section addressing the economic contribution of pastoralism, which introduces the concept of total factor productivity as a suitable approach for properly measuring the productivity of pastoral systems, and this section discusses in terms of:- employment and income; government revenue and exports; source of food; non-food outputs; inputs for sustainable agriculture; efficient and environmentally sustainable use of scarce and marginal resources. The second section assesses the problems that constrain the Development of pastoral system; finally conclusions are given in the last section.